Antibiotic Practices and The Rate of Surgical Site Infection Following Cesarean Section - Hussein, Maiga Ayub; Sutiningsih, Dwi; Saidi, Ntambi; Frida, Chebet; Adi, Mateus Sakundarno (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Cesarean section (CS) is the most performed operation globally. It’s a clean-contaminated surgery with higher surgical site infections (SSIs) risk. The mortality rate associated with cesarean section in Africa is 50 times greater than in high income settings, 11 women die per 1000 CS in sub-Saharan Africa and 14% of women suffer complication (SSIs). Proper antibiotic use can reduce this burden however effective antibiotics are running out due to inappropriate use. This study aimed to assess the pre-cesarean and post-cesarean antibiotic practices and the rate of SSIs following CS at Mbale regional referral hospital (MRRH)Methods: The study was a retrospective and descriptive cross-sectional on CS mothers between 1st January 2020 and 31st December 2022 at MRRH. Out of the 2432 patient files reviewed, an equal number (104) of women who developed SSIs and those that did not develop SSIs (104) were selected by simple random sampling, total sample size of 208.Result: More than half (n=148; 71.2 %.) received antibiotic prophylaxis. Majority received I.V ceftriaxone (38.0%) within 15minutes (mean duration) before skin incision. 35.1% of 208 that received antibiotic prophylaxis developed SSIs. I.V Metronidazole and Ceftriaxone were the most administered after CS and Oral metronidazole was the most prescribed upon discharge.Conclusion : The rate of SSIs at MRRH was 3% similar to that of Mbarara regional referral hospital at 3.5%. Lack of antibiotics prophylaxis and poor antibiotic prophylaxix timing could explain this rateu underscoring compliance to International, National and Hospital surgical bundles.